1970
DOI: 10.1099/00221287-60-2-191
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Two Techniques for Counting Cellulolytic Rumen Bacteria

Abstract: S U M M A R YCellulolytic bacteria were counted by the ' direct' method; estimated from the number of clearings produced in films of cellulose-containing agar medium inoculated with high dilutions of rumen ingesta and by the 'indirect' method; numbers were calculated from 'total culturable' counts on films of a non-specific agar medium and from the percentages of bacteria found to be cellulolytic after isolation in pure culture. The two methods yielded similar results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1977
1977
2012
2012

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 11 publications
(6 reference statements)
0
12
0
Order By: Relevance
“…Since cellulose is the major part of the ruminant diet, cellulolytic bacteria have been the targets of much interest. Several methods have been developed to determine the number of cellulolytic microorganisms in the rumen (Bryant and Robinson, 1961;van Gylswyk, 1970;Teather and Wood, 1982). Their nutritional requirements have been discussed in many papers [see the above-mentioned reviews and Bryant (1973)].…”
Section: 4lc Anaerobic Cellulolytic Bacteria Of Rumen and Intestinalmentioning
confidence: 99%
“…Since cellulose is the major part of the ruminant diet, cellulolytic bacteria have been the targets of much interest. Several methods have been developed to determine the number of cellulolytic microorganisms in the rumen (Bryant and Robinson, 1961;van Gylswyk, 1970;Teather and Wood, 1982). Their nutritional requirements have been discussed in many papers [see the above-mentioned reviews and Bryant (1973)].…”
Section: 4lc Anaerobic Cellulolytic Bacteria Of Rumen and Intestinalmentioning
confidence: 99%
“…In an earlier study [8] no appreciable differences were found when numbers of cellulolytic rumen bacteria were estimated by either a direct or an indirect counting method. However, it was subsequently shown that with the direct method the number of cellulolytic bacteria is underestimated because B. succinogenes, an important component of the cellulolytic flora, does not produce clearings in cellulose agar medium [5].…”
Section: Discussionmentioning
confidence: 81%
“…We also present the results of an experiment on longevity of newly isolated strains of B. succinogenes in agar medium which could explain why we did not find appreciable differences in cellulolytic counts in the rumen of sheep when using 2 different counting techniques in another study [8].…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations